PERIPHERAL NERVOUS SYSTEM LESSON IN CORONAVIRUS INFECTION COVID-19 - Ya.N. Majidova; N.M. Azimova; M.K. Temirova (International Scientific and Current Research Conferences, 2021)
Infection caused by the SARS-CoV-2 (COVID-19) coronavirus, accompanied by various lesions of various organs and body systems, is associated with a certain level of mortality, especially in the presence of risk factors [1]. The interest of neurologists in this disease is due to the frequent defeat of various parts of the central and peripheral nervous system (PNS), reports of which appeared in the medical literature already in the first half of 2020.